2009
DOI: 10.3803/jkes.2009.24.4.272
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Graves' Disease with Pancytopenia

Abstract: Hematological disorders, and especially single lineage abnormalities, have been described in patients suffering with thyrotoxicosis, but pancytopenia is a rare complication of thyrotoxicosis. Pancytopenia with thyrotoxicosis has been reported to be totally reversible with antithyroid drug treatment. We experienced a case with pancytopenia associated with Graves' disease in a 57-year-old woman who had no specific cause of pancytopenia. She presented with dyspnea and palpitation. The laboratory findings revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…9 It is suggested that a cross antigenicity between human TSH receptors and polynuclear neutrophils, a decreased circulating time of granulocytes, and a reduced marrow granulocyte reserve are the causes of neutropenia in thyrotoxicosis. 7,10 In this case, lymphocyte values were not compatible with Kocher's blood picture. And excessively corrected leukopenia was caused by short-term use of steroids in the early.…”
Section: Discussionmentioning
confidence: 64%
“…9 It is suggested that a cross antigenicity between human TSH receptors and polynuclear neutrophils, a decreased circulating time of granulocytes, and a reduced marrow granulocyte reserve are the causes of neutropenia in thyrotoxicosis. 7,10 In this case, lymphocyte values were not compatible with Kocher's blood picture. And excessively corrected leukopenia was caused by short-term use of steroids in the early.…”
Section: Discussionmentioning
confidence: 64%
“…Some autoimmune processes are also suspected of gradually affecting the bone marrow stem cells due to excess hormone secretion [ 9 , 10 ]. According to the literature, 22% of Graves’ disease patients have anemia [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…[28] It has been suggested that a cross antigenicity between TSH receptors and polynuclear neutrophils, a decreased circulating time of granulocytes and reduced marrow granulocyte reserve are the causes of neutropenia in thyrotoxicosis. [29,30] However, these still remain controversial .When slight leucopenia, neutropenia and thrombocytopenia are common manifestations of Graves disease even in untreated cases and believed to be an autoimmune process, use of anti-thyroid medications mainly Thiamazole could cause serious life-threatening agranulocytosis. This critical condition however occurs only in 1% of patients within the 1st few weeks or months of the treatment.…”
Section: Discussionmentioning
confidence: 99%